Nanoporous spongy graphene: Potential applications for hydrogen adsorption and selective gas separation - Kostoglou, Nikolaos; Constantinides, Georgios; Charalambopoulou, Georgia Ch; Steriotis, Th; Polychronopoulou, Kyriaki; Li, Yuanqing; Liao, Kin; Ryzhkov, Vladislav; Mitterer, Christian; Rebholz, Claus (My University, 2015)
In the present work, a nanoporous (pore width ~ 0.7 nm) graphene-based sponge-like material with large surface area (~ 350 m2/g) was synthesized by wet chemical reduction of graphene oxide in combination with freeze-drying. Surface morphology and elemental composition were studied by scanning and transmission electron microscopy combined with energy dispersive X-ray spectroscopy. Surface chemistry was qualitatively examined by Fourier-transform infrared spectroscopy, while the respective structure was investigated by X-ray diffraction analysis. Textural properties, including Brunauer-Emmet-Teller (BET) surface area, micropore volume and surface area as well as pore size distribution, were deduced from nitrogen gas adsorption/desorption data obtained at 77 K and up to 1 bar. Potential use of the spongy graphene for gas storage and separation applications was preliminarily assessed by low-pressure (0-1 bar) H2, CO2 and CH4 sorption measurements at different temperatures (77, 273 and 298 K). The adsorption capacities for each gas were evaluated up to ~ 1 bar, the isosteric enthalpies of adsorption for CO2 (28-33 kJ/mol) and CH4 (30-38 kJ/mol) were calculated using the Clausius-Clapeyron equation, while the CO2/CH4 gas selectivity (up to 95:1) was estimated using the Ideal Adsorbed Solution Theory (IAST).
Keywords: Freeze drying; Gas selectivity; Gas sorption; Graphene; Nanoporous sponge; Wet reduction